Respuesta :

Answer:  The answer is f(g(5)).


Step-by-step explanation:  We are given to write the expression which is equivalent to (fg)(5), where f(x) and g(x) are two functions.

We write the expression as follows:

(fg)(x) = f(g(x)), so that (fg)(5) = f(g(5)). That is, first we will evaluate g(5), whatever the value we get, we will find f of that value. to reach at our result.

For example,

if f(x) = x+3, and g(x) =  x²+1, then

(fg)(x) = f(g(x)) = f(x²+1) = x²+1+3 = x²+4.

Hence, (fg)(4) = f(g(4)) = f(17) = 17 + 3 = 20.

Thus, (fg)(5) = f(g(5)).